2023
DOI: 10.1038/s41598-023-48094-5
|View full text |Cite
|
Sign up to set email alerts
|

Music compensates for altered gene expression in age-related cognitive disorders

Alberto Gómez-Carballa,
Laura Navarro,
Jacobo Pardo-Seco
et al.

Abstract: Extensive literature has explored the beneficial effects of music in age-related cognitive disorders (ACD), but limited knowledge exists regarding its impact on gene expression. We analyzed transcriptomes of ACD patients and healthy controls, pre-post a music session (n = 60), and main genes/pathways were compared to those dysregulated in mild cognitive impairment (MCI) and Alzheimer’s disease (AD) as revealed by a multi-cohort study (n = 1269 MCI/AD and controls). Music was associated with 2.3 times more whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 64 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Music, as an artistic manifestation, offers a profound impact on the emotional, cognitive and physiological aspects of personal experiences. 36 Some studies have shown that music therapy has a positive impact on individuals with decreased cognitive function, helping improve objective and subjective cognitive functions, such as subjective memory function. 37 Reminiscence therapy is also one of the common methods used to improve cognitive function in the elderly, which helps stimulate autobiographical memory and simultaneously improve mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Music, as an artistic manifestation, offers a profound impact on the emotional, cognitive and physiological aspects of personal experiences. 36 Some studies have shown that music therapy has a positive impact on individuals with decreased cognitive function, helping improve objective and subjective cognitive functions, such as subjective memory function. 37 Reminiscence therapy is also one of the common methods used to improve cognitive function in the elderly, which helps stimulate autobiographical memory and simultaneously improve mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The Ethics Committee of Xunta de Galicia approved the present project (Registration code: 2020/021), and the study was conducted in accordance to the guidelines of the Helsinki Declaration. We have followed the same experimental procedures described in Gómez-Carballa et al (2) and within the framework of the Sensogenomics project (http://sensogenomics.com). Briefly, we collected saliva samples at two timepoints: before and after an experimental concert of classical music; see Figure 1 of (2) for a schematic representation of the sampling and analysis procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the exploratory study by Navarro et al (3) provided suggestive evidence of the potential impact of music in the context of Alzheimer’s disease (AD) and reviewed the current evidence overall, concurring on the beneficial effect of music on neurodegenerative diseases. To the best of our knowledge, our most recent study, Gómez-Carballa et al (2), is the only attempt to date to examine the impact of music in a disease context, specifically in capillary blood samples collected from age-related cognitive disorder (ACD) patients. This study (2) found an increased effect of music in ACD patients compared to healthy controls, but most interestingly, it revealed that brief musical stimuli can modify the way patients express genes typically altered in this condition, but in the opposite direction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations